A novel finite element method for simulating surface plasmon polaritons on complex graphene sheets - Li, Jichun; Neunteufel, Michael; Zhu, Li (Journal of computational physics, 2025)
Surface plasmon polaritons (SPPs) are generated on the graphene surface, and provide a window into the nano-optical and electrodynamic response of their host material and its dielectric environment. An accurate simulation of SPPs presents several unique challenges, since SPPs often occur at complex interfaces between materials of different dielectric constants and appropriate boundary conditions at the graphene interfaces are crucial. Here we develop a simplified graphene model and propose a new finite element method accordingly. Stability for the continuous model is established, and extensive numerical results are presented to demonstrate that the new model can capture the SPPs very well for various complex graphene sheets.